Probabilistic seismic hazard analysis of the North-East India towards identification of contributing seismic sources - Niranjan Borah; Abhishek Kumar (Geomatics, Natural Hazards & Risk, 2023)
AbstractThe North East (NE) India is regarded as one of the most seismically active regions of the globe. It is surrounded by two active plate boundaries (the Indian-Eurasian Plate boundary and the Indian-Burmese plate boundary), followed by rotation in the central part. As per the Seismic zonation map of India, most parts of NE India is classified under single seismic zone (zone V). However, numerous studies have shown significant variations in seismic activity as well as seismic hazard values across the NE. Present work attempts deaggregation of seismic hazard to identify seismic sources which control probabilistic seismic hazard values across the NE. With dominating fault mechanisms, seismic activity, and non-uniform past earthquake (EQ) records across NE, identifying controlling sources is crucial in order to understand the present and future seismic scenarios. Spatial distribution of seismic hazard levels and uncertainties are estimated using the Monte Carlo approach to sample a logic tree with alternate methods and models. As per the present findings, Manipur and Nagaland have highest seismic hazard in the NE, controlled by Indo-Burmese ranges. Further, seismic hazard of Guwahati, Shillong and Gangtok are significantly influenced by great EQs. In other parts, regional major to strong EQ sources control the seismic hazard values. Additionally, EQs with magnitude lesser than 4.5 have lower contributions to regional seismic hazards.